The analysis of competition infringements in RORO transportation in the light of sample cases from EU and Turkey - Tomur, Huriye Dilbeste (My University, 2019)
Deniz taşımacılığı farklı metodlarla yük taşınmasını elverişli hale getirdiğinden önemi son yıllarda artmıştır. Avrupa Birliği üye ülkelerinde deniz taşımacılığı alanında faaliyet gösteren şirketlerin artması ile deniz taşımacılığı önem kazanmıştır. Türkiye’de ise Avrupa Birliği kuralları ile uyumlaşmayı sağlamak için deniz taşımacılığı önemli hale gelmiştir. Buna bağlı olarak çeşitli rekabet hukuku ihlalleri de görülmeye başlanmıştır. Bu çalışma deniz taşımacılığının bir alt türü olan RORO taşımacılığına odaklanmıştır. Çalışmanın amacı rekabet ihlallerinin RORO taşımacılığında görünümlerini incelemektir. Hakim durumun kötüye kullanımı ve kartel oluşumu bu ihlallerin en tipik örnekleridir. Hakim durumun tespiti ve kötüye kullanımının belirlenmesi için şirketlerin pazar payı, faaliyet gösterdikleri ilgili pazar ve ekonomik davranışları incelenmiştir. Kartel oluşumunda ise şirketlerin ekonomik kararlarının, ilgili pazarı ve rakip firmaların faaliyetlerini etkileme düzeyi incelenmiştir. Etkili bir RORO taşımacılığı için bu ihlallerin yukarıda anılan unsurlar ışığında değerlendirilmesi gerekmiştir. RORO taşımacılığında adil ve etkili rekabetin sağlanabilmesi için ihlallerin yaptırımlara bağlanarak caydırıcı olması gerekmektedir. Avrupa Birliği ve Türkiye’den örnek dava analizleri ile bu sonuç pekiştirilmiştir.

In recent years, maritime transport has gained more importance as it is favorable in the carriage of products with different methods. The number of companies which deal with the marine carriage in the European Union has increased, and the maritime transport has started to play an essential role within the EU Member States. Aiming to achieve the harmonization of EU rules as a candidate state, Turkey has started to take cognizance of marine transport. Accordingly, various competition infringements have been occurring in this field. The thesis is primarily focused on RORO transport as a subbranch of maritime transportation. The thesis aims to examine the competition infringements in RORO transport. Abuse of a dominant position and cartel infringements are the most known types of such competition breaches. The market shares of the companies, relevant market, and economic behaviors are analyzed to detect the dominance as well as the abuse of a dominant position. The financial decisions of firms are examined under the cartel infringement, whether such decisions are able to affect the market and the competitors negatively. To ensure effective RORO transport, the elements mentioned above must be analyzed. The protection of fair competition and an effective competitive environment requires various sanctions as a disincentive. This requirement is underpinned by the sample cases from the EU and Turkey.
Keywords: abuse of a dominant position; Avrupa Birliği; cartel; European Union; hakim durumun kötüye kullanılması; Hukuk; kartel RORO transport; Law; RORO taşımacılığı; Transportation; Ulaştırma